Pengaruh Brand Awareness, Transparansi dan Kepercayaan Dalam Menyalurkan ZIS Di Aplikasi kitabisa.com: (Studi Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar) - Wardy Putra, Trisno; Abidah, Nurul; Khaerunnisa, Ummu; Risma, Risma (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
In the digital era as it is today, it is no stranger to the people of the capital city with digital developments, especially in the financial sector, financial technology that offers many conveniences from helping buying and selling transactions to offering payment systems for social activities such as zakat, fundraising and donations. Therefore, the reason for making this research is to find out the extent of the influence of Brand Awareness, Transparency and Student Trust in distributing ZIS in the Kitabisa.Com application. This study uses quantitative methods where this study uses primary data through questionnaires and secondary data from various sources such as journals, theses and related articles. So that the hypothesis in this test is accepted, it means that simultaneously the independent variables have a real influence on the dependent variable and together the Independent variables (brand awareness, transparency and trust) have a significant effect on Y (the decision to distribute ZIS on the Kitabisa.Com application)